Identification of Vocational Well-being Taxonomy For TVET Sustainable Growth: An initial review - LAMBIN, REGINA; MUSTAPHA, RAMLEE; SHARIF, MP ROSLIN MD (The journal of contemporary issues in business and government, 2021)
The Industrial Revolution 4.0 (IR4.0) era has changed the working environments and the expertise of many professions rapidly. This 21st Century is a daunting period for all the workforce because it requires a new technical and soft skills suite. Thus, this study aims to identify the Vocational Wellbeing Taxonomy (VWT) for sustainable growth of Technical Vocational and Education Training (TVET). TVET has a significant role in achieving and supporting sustainable growth. Its institutions are the primary supplier of the workforce that will be at the forefront in dealing directly with sustainability issues. As the rates of fresh-grade unemployment increase, students are more mindful of engaging in the vocational stream to ensure the workplace's well-being. Bloom's taxonomy has been used in an educational context to identify educational goals, objectives, and outcomes since 1956. However, it does not fulfil the 'well-being' assessment criterion for highly skilled workers with technical expertise. The concepts of well- being are closely linked to human capital that could be translated into individual skills, as highlighted in TVET. Therefore, the identification of VWT is crucial to provide a framework for the determination of objectives and evaluating learning outcomes relevant to vocational education. In this study, the VWT domains are expecting to contribute to the worker's well-being for the sustainable growth of TVET. This initial study employed a thorough review of the relevant literature.